2017
DOI: 10.1292/jvms.16-0406
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal changes in the relative abundance of intestinal <i>Lactobacillus</i> spp. in newborn calves

Abstract: The intestinal microbiota of newborn calves changes during the early postnatal period and influences their health and immune function. We studied the compositional changes in the intestinal microbiome of newborn calves during the first week after birth by metagenomic analysis. In feces from newborn calves, we identified 4 bacterial phyla, namely, Actinobacteria, Bacteroidetes, Firmicutes and Proteobacteria. The relative abundance of Lactobacillaceae significantly increased from day 1 to day 7. We evaluated Lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Recently, the first week of life has been reported to be an important period for the intestinal colonization of calves by LAB spp. [ 34 ]. Moreover, the administration of LAB spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the first week of life has been reported to be an important period for the intestinal colonization of calves by LAB spp. [ 34 ]. Moreover, the administration of LAB spp.…”
Section: Discussionmentioning
confidence: 99%
“…These include but are not limited to: diet, antibiotic treatment, environments for as growth and feeding, and stress. The period from birth to weaning is stressful to young calves, causes decreased immunity, and reduces calf herd productivity [ 29 , 34 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First systematic investigations on the development of bacteria in the gut of newborn calves were carried out in the early 1960s (Smith and Crabb 1961;Smith 1965). Although there are some publications dealing with the calf's intestinal microbiome, there are only a few studies that cover the development within the first week of life (Takino et al 2017;Song et al 2018). This is surprising, considering that enteric infections in neonatal calves are amongst the major causes of calf mortality during the early stage of life (Bendali et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…When meconium peritonitis occurs, early operation is a valid way to prevent the exacerbation of intra-abdominal inflammation, hyperemia and edema of the intestinal wall and intestinal adhesion, assisting in the reduction of severe infection and mortality. Takino T et al [13] pointed that the relative abundance of Firmicutes (including its families, such as Lactobacillaceae ), which supports health and immune function, was increased substantially during the first week after birth. Giri P et al [12] observed that the sympathoadrenal function could be affected by lack of a microbiome or microbial metabolites, leading to inferior health status.…”
Section: Discussionmentioning
confidence: 99%